Measuring quality for use in incentive schemes: The case of "shrinkage" estimators - Nirav Mehta (Quantitative Economics, 2019)
Researchers commonly "shrink" raw quality measures based on statistical criteria. This paper studies when and how this transformation's statistical properties would confer economic benefits to a utility-maximizing decision-maker across common asymmetric information environments. I develop the results for an application measuring teacher quality. The presence of a systematic relationship between teacher quality and class size could cause the data transformation to do either worse or better than the untransformed data. I use data from Los Angeles to confirm the presence of such a relationship and show that the simpler raw measure would outperform the one most commonly used in teacher incentive schemes.
Keywords: D81; I21; I28; J01; 330; Economics of education; empirical contracts; teacher incentive schemes; teacher quality